1995
DOI: 10.1074/jbc.270.13.7411
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Schizosaccharomyces pombe rae1 Gene Causes Defects in Poly(A)+ RNA Export and in the Cytoskeleton

Abstract: A collection of fission yeast Schizosaccharomyces pombe conditional mutants was screened for defective nucleocytoplasmic transport of poly(A)+ RNA by fluorescence in situ hybridization. We identified a temperature-sensitive mutant that accumulated poly(A)+ RNA in the nucleus and have named it rae1-1, for ribonucleic acid export. All rae1-1 cells exhibit the defect in poly(A)+ RNA export within 30 min following a shift to the non-permissive temperature. In addition, in the rae1-1 mutant, actin and tubulin becom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
162
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 143 publications
(169 citation statements)
references
References 38 publications
6
162
1
Order By: Relevance
“…Gle2p possesses striking amino acid sequence similarity to the protein encoded by RAE1, a gene required for normal poly(A)+ RNA export in S. pombe (Brown et al, 1995) It has been suggested that the rael-1 mutant RNA export phenotype in S. pombe cells is an indirect consequence of a role for Raelp in the cell cycle or cytoskeletal machinery (Brown et al, 1995). Our characterization studies in S. cerevisiae demonstrate both a genetic and physical basis for Gle2p function at the NPC.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…Gle2p possesses striking amino acid sequence similarity to the protein encoded by RAE1, a gene required for normal poly(A)+ RNA export in S. pombe (Brown et al, 1995) It has been suggested that the rael-1 mutant RNA export phenotype in S. pombe cells is an indirect consequence of a role for Raelp in the cell cycle or cytoskeletal machinery (Brown et al, 1995). Our characterization studies in S. cerevisiae demonstrate both a genetic and physical basis for Gle2p function at the NPC.…”
Section: Discussionmentioning
confidence: 70%
“…Alignment of the sequences gave an overall match of 82% (with 52% identical and 32% similar). The four putative ,B-transducin/WD repeats in Raelp (Brown et al, 1995) are largely conserved in Gle2p (underlined, Figure 2B). Mutation of the glycine residue at position 219 in Raelp to glutamic acid results in a temperaturesensitive RNA export mutant (Brown et al, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations